Pengaruh Penggunaan Tepung Maggot (Hermetia illucens) dalam Ransum terhadap Kualitas Karkas Ayam Petelur Jantan Belah Empat: Impact of Maggot Meal (Hermetia illucens) in Diets on Carcass Quality of Quartered MaleLayer Chickens - Kususiyah, Kususiyah; Emzelina Sary Damanik; Desia Kaharuddin; Anggun Marisa (BPFP Universitas Bengkulu, 2025)
This study aimed to evaluate the effect of maggot meal (Hermetia illucens) inclusion in the diet on the carcass quality of quartered male layer chickens. A Completely Randomized Design was used, consisting of four treatments with five replications, each replication using eight Lohmann Brown male layer chickens. The treatments differed in the inclusion levels of maggot meal: 0% (P0), 4% (P1), 8% (P2), and 12% (P3). Observed variables included slaughter weight, carcass weight, carcass percentage, abdominal fat percentage, meat color, meat bone ratio, cooking loss, and drip loss. Data were analysed using Analysis of Variance, and significantly different results (P<0.05) were further tested using Duncan’s Multiple Range Test to determine differences among treatments. The results showed that maggot meal inclusion had no significant effect (P>0.05) on carcass percentage, abdominal fat percentage, meat bone ratio, and drip loss. However, it significantly affected (P<0.05) slaughter weight, carcass weight, meat color score, and cooking loss. Slaughter weight, carcass weight, and meat color scores in P0, P1, and P2 were higher than in P3, while cooking loss in P0, P1, and P2 was lower than in P3. It can be concluded that maggot meal inclusion up to 8% does not reduce the carcass quality of quartered male layer chickens, whereas 12% inclusion decreases slaughter weight, carcass weight, and meat color score, and increases cooking loss without affecting drip loss.